Ignorance/ Denial-Fear/ Paralysis/ Engagement/ Commitment: Reflections on a Decade Teaching Climate Change Law - Stein, Eleanor (Radical Teacher, 2015)
Teaching about climate change at any level means introducing students to the fearsome realities of our rapidly changing earth. But more than transmitting curriculum content, this teaching requires opening a space where students can investigate, research and interrogate the logic of the media, corporate, and government discourse on climate change.